2009
DOI: 10.1002/stem.226
|View full text |Cite
|
Sign up to set email alerts
|

A Mesenchymal-Like ZEB1+ Niche Harbors Dorsal Radial Glial Fibrillary Acidic Protein-Positive Stem Cells in the Spinal Cord

Abstract: In humans and rodents the adult spinal cord harbors neural stem cells located around the central canal. Their identity, precise location, and specific signaling are still ill-defined and controversial. We report here on a detailed analysis of this niche. Using microdissection and glial fibrillary acidic protein (GFAP)-green fluorescent protein (GFP) transgenic mice, we demonstrate that neural stem cells are mostly dorsally located GFAP(+) cells lying ependymally and subependymally that extend radial processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
187
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(205 citation statements)
references
References 50 publications
16
187
2
Order By: Relevance
“…However, despite this evolutionary conservation, their function has not yet been fully elucidated. Gata2 + neurons of the central canal in newborn and young mice exhibit molecular and physiological characteristics of immature neurons, in agreement with previous observations (Stoeckel et al, 2003;Marichal et al, 2009;Sabourin et al, 2009;Orts-Del'Immagine et al, 2014Kútna et al, 2014).…”
Section: Heterochronic Development Of Csf-cns In Vertebratessupporting
confidence: 92%
See 2 more Smart Citations
“…However, despite this evolutionary conservation, their function has not yet been fully elucidated. Gata2 + neurons of the central canal in newborn and young mice exhibit molecular and physiological characteristics of immature neurons, in agreement with previous observations (Stoeckel et al, 2003;Marichal et al, 2009;Sabourin et al, 2009;Orts-Del'Immagine et al, 2014Kútna et al, 2014).…”
Section: Heterochronic Development Of Csf-cns In Vertebratessupporting
confidence: 92%
“…In the spinal cord, the ependymal area surrounding the central canal comprises ependymocytes and several other cell types (Bruni, 1998;Meletis et al, 2008;Sabourin et al, 2009;Marichal et al, 2012). Cells located by the central canal, show a robust expression of the transcription factor Nkx6-1 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, as observed for neurospheres that were derived from different brain regions (Armando et al 2007;Conti and Cattaneo 2010), neurospheres derived from different parts of the spinal cord have different growth and differentiation properties (Kulbatski and Tator 2009;Sabourin et al 2009). We showed that neurospheres that were derived from the cervical, thoracic and lumbar regions maintained their expression of specific and different rostro-caudal combinations of developmental homeogenes of the Hox family.…”
mentioning
confidence: 94%
“…To identify proliferating cells, we performed immunohistochemistry either for cell cycle S-phase marker 5-bromo-2-deoxyuridine (BrdU) or for the nuclear protein Ki-67, a marker expressed at all stages of the cell cycle. Both markers were previously used to detect cell division in parenchyma and CC region of the spinal cord in rodents [16,17].…”
Section: Introductionmentioning
confidence: 99%